PREVENTION OF CRIMINAL ACTS OF SEXUAL VIOLENCE AGAINST CHILDREN - Samsuria Samsuria; Andi Purnawati (Omnibus Law Journal, 2021)
In handling criminal acts of violence against minors, nowadays it still really needs special attention, considering that along with the progress of the times and various forms of sexual violence against minors that involve not only distant people but also in the scope of law enforcement is still very minimal. So far, the handling process is more about punishment for perpetrators of sexual violence, but also forgetting how the impact on victims, in this case children, is psychologically dependent. And also preventive measures that must be applied in social life in the community, many parties must be directly involved, not only the responsibility of the environment, the government, more specifically the role of parents and the family environment that. The method used in this research is a normative juridical approach, namely by conducting research based on legal / reference materials by examining theories and concepts from these legal materials, which relate to the legal principles of legislation. -Invitations related to this writing/research.